Business communications 98/99, fourth edition - Misiura, Shashi ([S.l.] : Butterworth-Heinemann, 1998)
The latest, fully updated edition of this popular workbook, containing the most recent exam questions and specimen answers from the senior examiner. Written to help you pass your exam first time, the text is lively and interactive. Each Unit has a similar structure to make learning easier and more consistent. Units contain: * Unit objectives to make planning your time easier * Tasks to help you test what you have learnt * Practical examples and case studies to relate theory to practice * Helpful questions to test your knowledge * Where to find out more in case you're stuck * Succinct Chapter summary * Revision tips to get you through the exam.
Keywords: business communications